Besökarstudie i Kilsbergens rekreationsområden : en metod för att utveckla rekreationsmöjligheter på Sveaskogs marker - Fransila, Johanna (SLU/Dept. of Forest Products, 2003)
In this Master thesis an effective method is presented to find out what is requested in a forest or outdoor recreation. The aim with the study is to find out how Sveaskog can increase the general interest for experiences in nature and improve the access for recreation. Some questions that have been used to answer this purpose are: Who is visiting/not visiting the recreation area? How is it possible to increase the number of visits? The study is carried out in Kilsbergen and mainly centered around Ånnaboda, which is the natural place for people to meet at and undertake recreational activities.